Ingested plastic and trace element concentrations in Short-tailed Shearwaters (Ardenna tenuirostris). (June 2020) - Puskic, Peter S.; Lavers, Jennifer L.; Adams, Louise R.; Bond, Alexander L.
Abstract: Pollution of marine environments is concerning for complex trophic systems. Two anthropogenic stresses associated with marine pollution are the introduction of marine plastic and their associated chemicals (e.g., trace elements) which, when ingested, may cause harm to wildlife. Here we explore the relationship between plastic ingestion and trace element burden in the breast muscle of Short-tailed Shearwaters ( Ardenna tenuirostris ). We found no relationship between the amount of plastic ingested and trace element concentration in the birds' tissues. Though the mass and number of plastic items ingested by birds during 1969–2017 did not change significantly, trace element concentrations of some elements (Cu, Zn, As, Rb, Sr and Cd), appeared to have increased in birds sampled in 2017 compared to limited data from prior studies. We encourage policy which considers the data gleaned from this sentinel species to monitor the anthropogenic alteration of the marine environment. Graphical abstract: Unlabelled Image Highlights: Short-tailed Shearwaters are one of the most studied seabirds for plastic pollution. Trace element burden is not monitored in fledglings of this sentinel species. Plastic ingestion rates for this species remain consistent with previous studies. Trace element burden has increased since the last study, six years ago. Monitoring that engages legislators & communities who consume these birds is needed.